Using bioinformatics tools to mine genes encoding 6-phospho-β-glucosidase from metagenomic data of bacteria surrounding white-rot fungi - Nguyen, Thi Binh; Le, Thi Thu Hong; Truong, Nam Hai (Vietnam Journal of Biotechnology, 2026)
6-Phospho-β-glucosidase (EC 3.2.1.86) is an enzyme involved in the hydrolysis of lignocellulose. It cleaves phosphorylated cellobioses to release glucose and glucose-6-phosphate. Therefore, identifying enzyme candidates with novel properties is crucial for enhancing the efficiency of lignocellulose hydrolysis. In this study, we mined 1718 open reading frames (ORFs) encoding 6-phospho-β-glucosidase from the DNA metagenome of bacteria in soil surrounding white-rot fungi, using the KEGG database. Of these, 1699 ORFs were classified as bacteria, 1633 ORFs (96.12%) were classified into three major bacterial phyla: Proteobacteria (1494 ORFs, 87.93%), Firmicutes (126 ORFs, 7.42%), and Actinobacteria (13 ORFs, 0.77%). Interestingly, the most abundant class was Gammaproteobacteria, which accounted for 86.64% of the Proteobacteria phylum, and Enterobacterales was the most dominant order (81.40%). Among the 1718 mined ORFs, 213 were complete, and 210 encoded proteins with functional regions. Of these, 152 ORFs contained the GH1 domain (84.87% from Proteobacteria), and 58 ORFs contained the GH4 domain (94.83% from Proteobacteria). The representative proteins had 28-39% alpha helices, 12-14% beta strands, and 2-4% disordered regions. The spatial structure models of these proteins were based on a published 6-phospho-β-glucosidase template, with 88-95% coverage and 100% confidence. The expression levels of the ORFs in E. coli were predicted using Periscope software. Two ORFs with the GH1 domain and three ORFs with the GH4 domain, from the Proteobacteria and Firmicutes phyla, showed high expression levels ranging from 904 mg/l to 4714 mg/l. All five selected enzymes were alkaline, with optimal enzyme activity at relatively high temperatures. These findings suggest that these enzymes hold significant potential for experimental designs aimed at industrial applications.